Assessment of a continuous-flow atmospheric air dielectric barrier discharge in the degradation of tramadol, cefixime, and carbamazepine in aqueous solutions - Samuel, Iwarere (University of Pretoria, 2024)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2024.